The role of HPV RNA transcription, immune response-related gene expression and disruptive TP53 mutations in diagnostic and prognostic profiling of head and neck cancer. - Wichmann, G.; Rosolowski, M.; Krohn, K.; Kreuz, M.; Boehm, A.; Reiche, A.; Scharrer, U.; Halama, D.; Bertolini, J.; Bauer, U.; Holzinger, D.; Pawlita, M.; et al. (Int J Cancer, 2015)
Stratification of head and neck squamous cell carcinomas (HNSCC) based on HPV16 DNA and RNA status, gene expression patterns, and mutated candidate genes may facilitate patient treatment decision. We characterize head and neck squamous cell carcinomas (HNSCC) with different HPV16 DNA and RNA (E6*I) status from 290 consecutively recruited patients by gene expression profiling and targeted sequencing of 50 genes. We show that tumors with transcriptionally inactive HPV16 (DNA+ RNA-) are similar to HPV-negative (DNA-) tumors regarding gene expression and frequency of TP53 mutations (47%, 8/17 and 43%, 72/167, respectively). We also find that an immune response-related gene expression cluster is associated with lymph node metastasis, independent of HPV16 status and that disruptive TP53 mutations are associated with lymph node metastasis in HPV16 DNA- tumors. We validate each of these associations in another large data set. Four gene expression clusters which we identify differ moderately but significantly in overall survival. Our findings underscore the importance of measuring the HPV16 RNA (E6*I) and TP53-mutation status for patient stratification and identify associations of an immune response-related gene expression cluster and TP53 mutations with lymph node metastasis in HNSCC.
Keywords: Carcinoma, Squamous Cell/immunology/mortality/secondary/*virology; Gene Expression Regulation, Neoplastic/immunology; Gene Frequency; Head and Neck Neoplasms/immunology/mortality/pathology/*virology; Human papillomavirus 16/genetics/*immunology/metabolism; Humans; Immunity, Innate/genetics; Lymphatic Metastasis; Mutation; Papillomavirus Infections/*immunology/mortality/pathology; Prognosis; Proportional Hazards Models; RNA, Viral/*genetics/metabolism; Transcription, Genetic; Tumor Suppressor Protein p53/*genetics